2017
DOI: 10.1039/c7nr05687g
|View full text |Cite
|
Sign up to set email alerts
|

Improved efficient perovskite solar cells based on Ta-doped TiO2nanorod arrays

Abstract: Organometal halide perovskite solar cells (PSCs) are nowadays regarded as a rising star in photovoltaics. In particular, PSCs incorporating oriented TiO nanorod (NR) arrays as the electron transport layer (ETL) have attracted significant attention owing to TiO NR's superior electron transport abilities and its potential in long-term stable PSCs. In addition to improve the electron-transport ability of TiO NRs, the tuning of the band alignments between the TiO NR array and the perovskite layer is also crucial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 71 publications
0
44
0
Order By: Relevance
“…[15][16][17] As a result, compromised charge transport efficiency and severe charge recombination at the perovskite/ETL interface was observed. 18 By comparison, well-oriented one-dimension (1-D) TiO2 nanorods/nanowires/nanotubes arrays represent a promising strategy, 14,[18][19][20][21][22][23][24][25][26][27][28][29][30] exhibiting less surface defects and grain boundaries and facilitating precursor pore-filling. 1D TiO2 arrays can thus provide a direct physical conductive paths to extract and transport efficiently carriers generated by the perovskite layer.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] As a result, compromised charge transport efficiency and severe charge recombination at the perovskite/ETL interface was observed. 18 By comparison, well-oriented one-dimension (1-D) TiO2 nanorods/nanowires/nanotubes arrays represent a promising strategy, 14,[18][19][20][21][22][23][24][25][26][27][28][29][30] exhibiting less surface defects and grain boundaries and facilitating precursor pore-filling. 1D TiO2 arrays can thus provide a direct physical conductive paths to extract and transport efficiently carriers generated by the perovskite layer.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, by using yttrium 17 doped TiO 2 as compact layer, the charge extraction process was improved and the planar PSC device achieved a high PCE of 19.3%. Up to now, magnesium, 18 lithium or sodium, [19][20][21][22] samarium, 23 lanthanum, 24 tantalum, 25 uorine, 26 thallium, 27 and other metal [28][29][30] doped TiO 2 have been attempted in perovskite solar cells. Niobium-doped TiO 2 (Nb:TiO 2 ) has been tremendous used in transparent conductive oxides (TCOs), 31 photocatalysis, 32,33 lithium and sodium ion batteries, 34,35 dyesensitized solar cells (DSSCs).…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have been published to explain the influence and benefit of appropriate doping in TiO 2. [34][35][36][37][38][39] In our early research, we also revealed that Zn-doped TiO 2 can significantly raise the electron extraction ability and align energy level well with perovskite. [28,29] Accordingly, we chose Zn as a dopant and design synthesis route to obtain Zn:LT-TiO 2 NCs.…”
Section: Zn Doping In Lt-tiomentioning
confidence: 99%